Web-based Administrative Information System at the Sei Sikambing B Village Office - Prayoga, J.; Hasugian, Buyung Solihin; Rusydi, Ibnu (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Administrative services at the sub-district office play an important role in supporting the effectiveness of public services. However, the manual systems that are still widely used often cause problems such as delays in processing, recording errors, and a lack of data transparency. This study aims to design and implement a web-based Administrative Information System at the Sei Sikambing B Sub-district Office to improve the efficiency and accuracy of administrative services. The system development method used is the Waterfall model, starting from needs analysis, system design, implementation, to testing. This system provides digital services for managing correspondence, population data, and document archives, featuring user login, notifications, and automatic document printing. Testing results indicate that this web-based system can accelerate administrative processes, reduce recording errors, and simplify data tracking for both staff and the public. With the implementation of this system, it is hoped that public services at the Sei Sikambing B Village Office will become more effective, transparent, and responsive to residents' needs.